STRUCTURING OF SUSTAINABILITY-LINKED DEBT FINANCING : Case: Sustainability-Linked Financing Framework for Metso Outotec Oyj - Manninen, Olli (My University, 2021)
This research was conducted as an assignment for a Finnish industrial company, Metso Outotec Oyj. Sustainable finance has gained a lot of attention recently and sustainable finance instruments, such as green and social bonds, have seen a surge in new issuance as ESG related considerations have become increasingly important for issuers and investors. Majority of the issued sustainable capital has come from use-of-proceeds bonds that require the proceeds to be earmarked to sustainability compatible assets or projects. In June 2020 ICMA published a set of guiding principles for Sustainability-linked bonds, which are a new performance-based debt instruments which financial characteristics will vary depending on whether the issuer achieves selected pre-defined sustainability key performance indicator (KPI) levels. Sustainability-linked Financing framework (SLFF) is a pre-issuance document that lays out the intended KPIs, targets, financial characteristics, verification and reporting for the future sustainability-linked financing transactions. Aim of the research was to support the establishment of Sustainability-linked Financing Framework that could be utilized in future bond, revolving credit facility and loan transactions. Research was conducted as case study where firstly, the SLB market and SLB frameworks were examined to build understanding of the emerging market practices. Secondly, Second Party Opinions assessing already published frameworks were examined in order to contextualize and evaluate the market guidance and best practices in relation to the concepts of materiality of and ambitiousness of the sustainability targets. Based on these findings a general KPI & target evaluation matrix with 13 factors was developed. After this, case company KPIs were evaluated utilizing the broader findings. Even though the product offers flexibility in terms of structuring, there exists a lot of similarities between issuers when it comes to the target setting and compensations mechanism. Materiality of the indicators is assessed mainly through the relevance to the issuers business and based on the extent the KPI is applicable for the impact. Ambitiousness of the targets is evaluated based on external reference, company's' own historical performance and peer performance. Several of the case company KPIs were found to be suitable for sustainability-linked financing. Some being stronger and some weaker, while all having different implications for the framework as an entity.

Tämä tutkielma on tehty toimeksiantona Suomalaiselle teollisuusyritykselle, Metso Outotec Oyj: lle. Kestävyytävän rahoituksen instrumentit kuten vihreät ja sosiaaliset joukkovelkirjalainat ovat nostaneet suosiotaan ja ESG-toimet nähdään yhä tärkeämpänä niin yrityksissä, kuin rahoitusmarkkinoillakin. Suurin osa kestävästä velkakirjarahoituksesta on laskettu liikkeelle instrumenteilla, jotka vaativat lainapääoman allokointia tiettyihin ennaltamääriteltyihin kestävän kehityksen hankkeisiin. Kesäkuussa 2020 ICMA julkaisi ohjaavat periaatteet kestävyyteen linkitetyille velkakirjoille (SLB), jotka ovat uusi kestävän rahoituksen instrumentti, jonka taloudelliset ominaisuudet vaihtelevat sen mukaan, saavuttaako liikkeeseenlaskija valitut ennalta määritellyt kestävän kehityksen avainindikaattorin (KPI) tasot. Kestävyyteen linkitetty rahoituskehys (SLFF) on liikkeeseenlaskua edeltävä dokumentti, jossa esitetään valitutt KPIt, niiden tavoitetasot, joukkovelkakirjan linkitetyt ominaisuudet, verifikaatio ja raportointi. Tutkimuksen tavoitteena oli tukea kestävyyteen linkitetyn rahoituskehyksen laatimista, jota voitaisiin tulevaisuudessa hyödyntää joukkovelkakirjalainoissa, valmiusluottolimiiteissä ja lainatapahtumissa. Tutkimus toteutettiin SLB markkinoita tutkivalla case-tutkimuksella, jossa tarkasteltiin jo liikkeellelaskettuja SLBita ja niiden vastaavia rahoitusviitekehyksiä. Ensiksi näitä tarkasteltiin ohjaavien periaatteiden tulkinnan ja kehittyvien markkinakäytäntäntöjen ymmärtämiskeksi ja toiseksi tarkasteltiin mittarieden kunnianhimoisuutta ja olennaisuutta kolmanne osapuolen antamia lausuntoja hyödyntäen. Näiden perusteella luotiin 13 osainen KPI sopivuus arviointi taulukko. Tämän jälkeen case-yrityksen KPI mittareita ja vastaavia tavoitteita arvioitiin kokonaisuudessaa löydösten valossa. Vaikka instrumentti mahdollistaa strukturoinnin hyvinkin erilaisilla tavoilla, liikkeeseenlaskijoiden välillä on paljon yhtäläisyyksiä tavoitteiden asettamisessa ja kompensaatio mekanismeissa. Indikaattorien olennaisuus arvioidaan lähinnä niiden merkityksellisyydestä liikkeeseenlaskijan liiketoiminnalle ja sillä missä määrin KPI on sovelttavissa näihin olennaisiin vaikutuksiin. Kunnianhimoisuus arvioidaan ulkoisen referenssin, historiallisen ja vertaisarvioinnin perusteella. Useat case yrityksen KPI:sta todettiin soveltuvan rahoitusviitekehykseen. Jotkut mittarit olivat tässä valossa vahvempia ja toiset heikompia, ja kaikilla oli erilaiset vaikutukset rahoituskehykseen kokonaisuutena.
Keywords: Sustainable finance, Sustainability-linked bond, Sustainability-linked financing, ESG, green bond, kestävä rahoitus, kestävyyteen linkitetty joukkovelkakirja, ESG, vastuullinen sijoittaminen